2011
DOI: 10.2106/jbjs.i.01321
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Techniques Versus Conventional Guides for Component Alignment in Total Knee Arthroplasty

Abstract: This study provides evidence that the implant alignment with computer-assisted total knee arthroplasty, as measured with radiography and computed tomography, is significantly improved compared with that associated with conventional surgery with intramedullary or extramedullary guides. This finding adds to the body of evidence showing an improved radiographic outcome with computer-assisted surgery compared with that following conventional total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 14 publications
3
85
1
Order By: Relevance
“…Long term, malalignment might increase the risk of loosening, instability, wear, and osteolysis [1-3, 6, 9, 18, 20, 24, 30-32]. After a decade of clinical use, computerassisted navigation has resulted in improved alignment but has not eliminated outliers and has not improved the clinical outcome [4,7,26,35]. One recent alternative has been the development of patient-specific instrumentation using MRI or CT imaging to generate patient-specific guides that can be used intraoperatively to control all six degrees of freedom of component alignment, which also controls limb and knee alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Long term, malalignment might increase the risk of loosening, instability, wear, and osteolysis [1-3, 6, 9, 18, 20, 24, 30-32]. After a decade of clinical use, computerassisted navigation has resulted in improved alignment but has not eliminated outliers and has not improved the clinical outcome [4,7,26,35]. One recent alternative has been the development of patient-specific instrumentation using MRI or CT imaging to generate patient-specific guides that can be used intraoperatively to control all six degrees of freedom of component alignment, which also controls limb and knee alignment.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many studies have investigated the accuracy of bone cuts in TKA according to many conventional guide systems and navigation systems and comparison of them. [7][8][9] Each cuts in TKA has its own special science and each cut can affect the other cuts and potentially the outcome of the TKA. [10] While coronal alignment and clinical outcome has been extensively investigated, the ideal alignment in sagittal plane has been mostly overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical assistance is becoming more frequently used in limb salvage surgery to preserve as much host tissue as possible without compromising tumor margins and may help surgeons perform more accurate resections [11,15,16,18]. However, previous reports about navigation in trauma and arthroplasty have suggested that computer assistance techniques do not improve patient-reported outcomes and that these techniques add surgical time [6,8,13,20]. Intraoperative problems and increased surgical time might be expected with the adoption of new technology, and a learning curve may apply to surgeons who attempt new methods like navigation [1,12,17].…”
Section: Introductionmentioning
confidence: 99%